Cholelithiasis in Children and Surgery Indication. A Case Report - Jorge Luís Estepa Pérez; Tahiluma Santana Pedraza; Juan Carlos Estepa Torres (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2012)
The case of a 9 years old male patient is presented. The patient is Bolivian, from Yacuiba, Tarija department and had a history of anemia in his infant stage. His mother brought him to the General Surgery Consultation in the '' Ruben Zelaya'' General Community Hospital because of dyspeptic stools, diarrhea and occasional abdominal pain with a 6 months evolution. Abdominal ultrasound was performed which confirmed the presence of gallstones, for which a cholecystectomy was performed. The patient evolved satisfactorily, thus allowing his hospitalary discharge in a 72 hours time lapse. Because of the weirdness of this case it was decided to have it published.